Being-in-context through live projects: including situated knowledge in community engagement projects - Abrahams, Clint; Delport, Hermie; Perold, Rudolf; Weber, Anna Marijke; Brown, James Benedict (Critical Studies in Teaching and Learning, 2023)
This paper explores the ‘live project’ as a pedagogical tool in architectural education in South Africa: one that allows educators and students, through pedagogies-in-context, to access and develop deeply situated knowledge(s) in the context of community engagement. We propose the concept of pedagogies-in-context as pedagogies in multiple overlapping contexts: the physical and social contexts of the higher-education institution, the intellectual, pedagogical, and political contexts of the curriculum, and the socio-economic contexts of educators, students, and communities. A live project allows for multiple ways of being-in-context – as students, educators, researchers, and community members. The paper employs an exploration of and critical reflection on one particular live project. Based on the critical reflection, we propose that in the South African context, live projects can be understood as enterprises to reconstitute situated knowledge(s), thereby empowering students and educators to rewrite their own experiences of learning and teaching by making meaningful connections with communities.